FACTORS IN THE DECISION TO ACCEPT THE COVID-19 VACCINATION: A LITERATURE REVIEW - Astarini, Made Indra Ayu; Lilyana, Maria Theresia Arie (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: The COVID-19 vaccination program was an effort made to prevent the transmission of the COVID-19 virus. Various considerations arise when this program was implemented. Individual factors are one of the factors that influence the decision to receive a COVID-19 vaccination. Objective: This literature review aims to review the factors related to the decision to receive the COVID-19 vaccination. Methods: The design used was literature review with PICO criteria (Population: General public (adult), Intervention: there no Intervention just to know the correlation, Comparison: there no comparison, Outcome: factor that correlate with decision to accept COVID-19 vaccination. Other criteria is the method: quantitative study) The keywords in two languages. The keywords for articles in Indonesian are